Genome-wide survey and expression analysis of the amino acid transporter superfamily in potato (Solanum tuberosum L.) - Ma, Haoli (Plant physiology and biochemistry : PPB, 2016)
Copyright © 2016 Elsevier Masson SAS. All rights reserved.